METODE STIMULUS FADING UNTUK MENURUNKAN GEJALA SELECTIVE MUTISM DISORDER PADA ANAK - Andi Ahmad Ridha (Jurnal Psikologi Integratif, 2019)
Abstract. The symptoms of selective mutism disorder in children cause it to be less able to speak in social situations where children are expected to speak. Interventions in the form of fading stimulus are expected to teach children new behaviors so that they are more adaptive in social situations. This study aims to determine the effectiveness of stimulus fading methods in reducing symptoms of selective mutism disorder in children. This study uses a single case experimental design with treatment in the form of the application of fading stimulus intervention in one 4-year-old boy who experienced symptoms of selective mutism disorder. The instruments of data collection were observation techniques of tallying behavior and rating scale, selective mutism questionnaire, and school speech questionnaire and analyzed descriptively. The results showed that after giving intervention within 10 days, the subject experienced significant progress, the subject became more expressive, could mingle and interact with others. Therefore, it can be concluded that the stimulus fading method can be used to reduce the symptoms of selective mutism disorder in children. Keywords: Children; Stimulus Fading; Selective Mutism Disorder Abstrak. Gejala selective mutism disorder pada anak menyebabkannya kurang mampu berbicara dalam situasi sosial dimana anak diharapkan dapat berbicara. Intervensi berupa stimulus fading, diharapkan dapat mengajarkan anak perilaku baru sehingga lebih adaptif dalam situasi sosial. Penelitian ini bertujuan untuk mengetahui efektivitas metode stimulus fading dalam menurunkan gejala selective mutism disorder pada anak. Penelitian ini menggunakan metode single case experimental design dengan perlakuan berupa penerapan intervensi stimulus fading pada satu orang anak laki-laki berusia 4 tahun yang mengalami gejala selective mutism disorder. Instrumen pengumpulan data berupa teknik observasi behavior tallying dan rating scale, selective mutism questionnaire, dan school speech questionnaire dan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa setelah pemberian intervensi selama dalam waktu 10 hari, subjek mengalami kemajuan yang signifikan, subjek menjadi lebih ekspresif, dapat berbaur dan berinteraksi dengan orang lain. Oleh karena itu, dapat disimpulkan bahwa metode stimulus fading dapat digunakan untuk menurunkan gejala selective mutism disorder pada anak.Kata kunci: Anak; Stimulus Fading: Selective Mutism Disorder